2020
DOI: 10.1111/odi.13462
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing periodontal disease: Oral manifestation of COVID‐19

Abstract: We read with interest the series of cases reported by Martín Carreras-Presas, Amaro Sánchez, López-Sánchez, Jané-Salas, and Somacarrera Pérez (2020). We believe that the described oral vesiculobullous manifestations were suggestive of coronavirus disease 2019 (COVID-19) co-infections, which, at present, are overlooked AUTH O R CO NTR I B UTI O N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
149
1
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(169 citation statements)
references
References 7 publications
1
149
1
18
Order By: Relevance
“…Palate 7,8,10,11,14 and the tongue 6,7,9,14 were the most frequent locations, followed by gums [10][11][12] and by lips. 10,11,14 Pain was referred by 75% of the patients [7][8][9]11,12,14 and 25% of them reported taste alterations. 6,8,11 In 42% of the reported cases, skin lesions were found.…”
mentioning
confidence: 98%
“…Palate 7,8,10,11,14 and the tongue 6,7,9,14 were the most frequent locations, followed by gums [10][11][12] and by lips. 10,11,14 Pain was referred by 75% of the patients [7][8][9]11,12,14 and 25% of them reported taste alterations. 6,8,11 In 42% of the reported cases, skin lesions were found.…”
mentioning
confidence: 98%
“…It is been found that Periodontal illness influence to a critical condition if the individual has other comorbidities [14]. It is suggested that there is a need of study to enquire the co-infection conditions among individuals who are affected with COVID-19 [15].…”
Section: Fig 1 Overview Of Periodontal Disease and Covid-19mentioning
confidence: 99%
“…Las comorbilidades de enfermedades cardiovasculares, pulmonares, diabetes y síndrome metabólico (todas éstas relacionadas bidireccionalmente con las enfermedades periodontales), exponen significativamente mayor gravedad y letalidad a quienes desarrollan COVID-19, esto tal vez se deba a una tormenta de citocinas representada por una sobrecarga de proteínas inflamatorias que acaban colapsando al sistema inmune 30 .…”
Section: Sacos Periodontalesunclassified